Analisis Bahasa Anies-Muhaimin pada Tayangan “Usai Putusan MK Anies-Muhaimin Menghormati dan Beri Selamat Ke Prabowo Gibran” di Channel Youtube Kompas TV Sukabumi - Hanif Mutiara Syifa; Ahmad Zamzamy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In political campaigns, rhetoric plays an important role to attract public attention. The Anies-Muhaimin candidate pair utilised the Youtube social media platform to campaign and discuss with the people through the